sCTLA-4, CD4+CD25+Foxp3+ regulatory T cells in Behcet's disease patients - Demir, N.; Ilhan, F.; Demir, T.; Godekmerdan, A. (Clinical & Exper Rheumatology, 2012)
[Abstract Not Available]
Keywords: Soluble Ctla-4; Receptor; Expression; Cd28; Cd86